Effect of early oral calcium supplementation on serum calcium and immunoreactive calcitonin concentration in preterm infants. Issue 8 (August 1980) - Sann, L; David, L; Chayvialle, J A; Lasne, Y; Bethenod, M
Abstract : Oral calcium supplements (80 mg/kg per 24 h) were given to 23 preterm infants, and the course of serum calcium, magnesium, immunoreactive calcitonin, and gastrin was compared with a control group of 23 matched infants. In the supplemented group, serum calcium concentrations remained at the baseline level (2.31 mmol/l +/- 0.18 SD) while a fall (from 2.27 +/- 0.18 to 1.91 +/- 0.24 mmol/l) was observed at 12-16 hours of age in the control group, with 4 values < 1.75 mmol/l. There was no change in serum magnesium concentration in either group. The postnatal rise of serum immunoreactive calcitonin concentrations in the control group (from 171 +/- 135 to 493 +/- 273 pg/ml at 12-48 hours of age) was not found in the supplemented group. There was a negative correlation between serum calcium and immunoreactive calcitonin levels in the control group, but not in the supplemented group. There was no correlation between serum immunoreactive calcitonin and gastrin concentrations. These data show that oral calcium supplementation can prevent early neonatal hypocalcaemia, and suggest that this effect is achieved at least in part through a reduction of the postnatal rise of serum immunoreactive calcitonin.